Města a vojáci v oblasti Opolska za třicetileté války - Kilián, Jan (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2018)
The article will focus on various aspects of the coexistence of urban residents from selected Silesian cities (in the area of today’s Opole) with soldiers of domestic and enemy armies during the Thirty Years’ War. Particularly, it will concentrate on the injustices and violence perpetrated, but also on the duties of the townspeople towards soldiers. However, it will also try to investigate the extent to which the experience of the cities was only negative or to trace the basis of possible cooperation between the cities, or further convergence. It also outlines the standard defence mechanisms cities developed over the long years of war to face the military burden.
Keywords: violence; towns; soldiers; Silesia; Thirty Years´ War; urban history; Opole region